International Developments in Atherosclerosis Disease Research Using Precision Medicine (1994–2024): A Bibliometric Analysis - Amukti, Danang Prasetyaning; Irham, Lalu Muhammad; Surono, Sugiyarto; Adikusuma, Wirawan; Riat El Khair; Rizky Gustinanda; Dilpreet Singh; Rockie Chong; Ilker Ates; Daraporn Rungprai (Scripta Medica, 2025)
Cardiovascular disease has risen to the leading cause of global death. Atherosclerosis (AS) is an important contributor to the development of cardiovascular disease, which is involved in the formation of atheromatous plaques on the walls of arteries, resulting in arterial stenosis. In the past two decades, the treatment approach has shifted from conventional methods to precision medicine, which aims to tailor medical interventions based on individual patient characteristics, including genetic information, biomarkers and environmental factors. A literature search of precision medicine research on atherosclerosis from 1994 to 2024 was conducted using the Scopus database. VOSViewer v.1.6.16 and Biblioshiny software programs were used to perform bibliometric analysis. Between 1994 and 2024, 482 documents were published from 299 different sources, with an average document age of 3.68 years and an average of 24.52 citations per document. The total number of authors involved was 3.141, with 40 of them writing the documents individually. Collaboration between authors was very prominent, with an average of 7.89 authors per document and 29.46 % of the documents involving international collaboration. The types of documents published were also diverse, including 187 articles, 1 book, 15 book chapters, 11 conference papers, 33 editorials, 1 erratum, 4 letters, 8 notes, 219 reviews and 3 short surveys. Global trends in precision medicine for atherosclerosis research from 1994 to 2024 showed that the field has undergone significant development. Precision medicine has great potential to improve the care of patients with atherosclerosis through a more personalised and data-driven approach. To maximise its benefits globally, international collaboration, investment in technology and education are needed to overcome existing barriers. Thus, precision medicine can bring significant changes to the research and treatment of atherosclerosis in the future.